2002
DOI: 10.1159/000067179
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Prolactin Improves Antitumor Effects of Murine Natural Killer Cells in vitro and in vivo

Abstract: Objective: To verify the effect of prolactin on natural killer (NK) cells in vivo and its implications for NK cell immunotherapy. Methods: Recombinant human prolactin (rhPRL; 30 µg, i.p.) was administered to BALB/c mice and severe combined immunodeficiency (SCID) mice 1 day before harvesting splenocytes for 51Cr release assay to examine the effects of rhPRL on NK cells of normal mice. rhPRL (10 µg, i.p., every other day for a total of 5 injections) was administered to BALB/c mice after syngeneic bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…They exerted their versatile roles in the defense of pathogens like murine cytomegalovirus (MCMV) [21,22] . Several studies also reported that hepatic NK and NKT cell took part in the antimetastasis of tumor [23][24][25] . NK1.1 + cells were reported to involve in the pathogenesis of many diseases, like human immunodeficiency virus (HIV) infection and liver disease [26,27] .…”
Section: Discussionmentioning
confidence: 96%
“…They exerted their versatile roles in the defense of pathogens like murine cytomegalovirus (MCMV) [21,22] . Several studies also reported that hepatic NK and NKT cell took part in the antimetastasis of tumor [23][24][25] . NK1.1 + cells were reported to involve in the pathogenesis of many diseases, like human immunodeficiency virus (HIV) infection and liver disease [26,27] .…”
Section: Discussionmentioning
confidence: 96%
“…The huPBL-SCID mouse has been demonstrated to be capable of mounting a human secondary Ig response to a variety of immunogens after immunization (31). Because rhPRL may improve the engraftment of human lymphocytes into lymphoid organs and promote general lymphocyte function, as reported previously (26,34), and the DT-specific proliferating response (Table 2) after in vivo treatment, we wanted to further observe if rhPRL acts as an adjuvant in DT immunization. It was noted that even without DT vaccine rechallenge, the baseline of DT-specific IgG was elevated after rhPRL treatment in huPBL-SCID mice ( Fig.…”
Section: Vol 14 2007 Prl Promotes Secondary Ig Response In Hupbl-scmentioning
confidence: 89%
“…Recombinant human prolactin was endotoxinfree and supplied as a gift by Dr. William J. Murphy, NCI-FCRDC, Frederick, MD, which has been used in their studies [22][23][24][25]. The IL-2-dependent NK cell line NK-92, established from a patient with rapidly progressive non-Hodgkin's lymophoma [26], was purchased from ATCC and maintained in a-MEM (Hyclone) medium containing100U/ml IL-2 and other necessary components as described [26].…”
Section: Cell Culture and Proliferation Assaymentioning
confidence: 99%
“…PRL also increased the proliferating response and cytotoxicity of human, murine or rat NK cells to sensitive or insensitive tumor independently or synergistically with IL-2 in vitro [17][18][19][20]. We previously reported that PRL improved the hematopoiesis and lymphocyte development in syngeneic bone marrow transplantation [21][22][23][24], and exerted anti-tumor effects on tumor-bearing mice in vivo [25]. However, thus far there has been little evidence indicating that PRL can directly affect NK cell function through prolactin receptor on human NK cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation